2012
DOI: 10.1182/blood-2012-01-401687
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming reverses the relapse-specific gene expression signature and restores chemosensitivity in childhood B-lymphoblastic leukemia

Abstract: Whereas the improvement in outcome for children with acute lymphoblastic leukemia has been gratifying, the poor outcome of patients who relapse warrants novel treatment approaches. Previously, we identified a characteristic relapse-specific gene expression and methylation signature associated with chemoresistance using a large cohort of matched-diagnosis relapse samples. We hypothesized that "reversing" such a signature might restore chemosensitivity. In the present study, we demonstrate that the histone deace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 48 publications
2
123
0
2
Order By: Relevance
“…Entinostat prolonged survival in leukemic mice as a single-agent to a similar level as that reported for continuous infusion of a potent small molecule inhibitor [44]. However, epigenetic priming agents, such as HDACis and hypomethylating molecules will most likely be more effective as part of a combined therapeutic approach in leukemia and cancer [45][46][47]. HDACis are associated with several modes of antitumor activity including modulation of the immune response [48], cell cycle arrest, promotion of differentiation, senescence, and apoptosis [46].…”
Section: Resultsmentioning
confidence: 57%
“…Entinostat prolonged survival in leukemic mice as a single-agent to a similar level as that reported for continuous infusion of a potent small molecule inhibitor [44]. However, epigenetic priming agents, such as HDACis and hypomethylating molecules will most likely be more effective as part of a combined therapeutic approach in leukemia and cancer [45][46][47]. HDACis are associated with several modes of antitumor activity including modulation of the immune response [48], cell cycle arrest, promotion of differentiation, senescence, and apoptosis [46].…”
Section: Resultsmentioning
confidence: 57%
“…With respect to basic cell culture experiments showing the influence of epigenetics on therapy responsiveness or resistance (101), recent data demonstrate that the epigenetic pre-treatment of human cancer cells induces differentiation and, therefore, presents us with a chance to improve the efficiency of classical chemotherapies (102). Therefore, we hypothesize that epigenetic therapy may stabilize the epithelial tumor phenotype or induce MET which may subsequently improve tumor sensitivity to conventional chemotherapy (Fig.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…A lower concentration of prednisolone was used in this experiment to avoid high levels of cell death associated with treating SAHA-pretreated cells with higher doses of prednisolone. It is not surprising that treatment with SAHA leads to decreased cell viability because SAHA has previously been shown to be toxic to leukemic cells (30,36); however, the restoration of GILZ induction in the TBL1XR1 knockdown cells does suggest that the impact of SAHA is mediated in part by the rescue of glucocorticoid signaling. These results are in agreement with the NCoR1 depletion studies showing the pivotal role of NCoR1 (and its associated HDACs) in mediating the GC resistance associated with loss of TBL1XR1.…”
Section: Tbl1xr1 Knockdown Results In Resistance Tomentioning
confidence: 99%
“…RS4;11 and UOCB1 cells have also been previously used to characterize pathways that mediate prednisolone sensitivity (27,28). It should be noted that although Reh cells have been characterized as having undetectable levels of GR (29), we have previously shown that Reh cells respond to steroid treatment comparably to primary patient samples, as well as other ALL cell lines, and express GR (30). We authenticated our parental Reh cell lines through short tandem repeat analysis by ATCC, and cytogenetic analysis confirmed the t(12;21), EVT6/RUNX1 translocation by cytogenetic analysis (data not shown).…”
Section: Tbl1xr1 Is Deleted With Decreased Gene Expression Atmentioning
confidence: 87%
See 1 more Smart Citation